Development of Learning Resources within Higher Education in Response to the Challenges of COVID 19 - Husam Helmi Alharahsheh; Afzal Sayed Munna; Sylvia Hoffmann; Anupam Mazumdar; Abraham Pius (International Journal of Asian Education, 2022)
This brief paper describes how additional learning resources can be developed at a module level within higher education. The context to further meet the requirements of a rapidly changing environment within the higher education context and to meet different trends and challenges such as employers’ expectations and challenges facing graduates to secure appropriate employment considering their disciplines. The case study reflects key considerations to ensure further students’ success as universities in the UK shifted from face-to-face delivery to quick online delivery due to the challenges presented by the Covid-19 virus spreading in the UK and Globally. In addition, the case study provides key considerations during the curriculum development process, such as constructive alignment, students’ backgrounds and diversity, and utilization of additional resources at the organizational level, such as Library Services and IT